1997
DOI: 10.1007/bf02465093
|View full text |Cite
|
Sign up to set email alerts
|

Indications for and results of splenectomy in different hematological disorders

Abstract: The objective of this retrospective study was to determine the indications for splenectomy in hematological disorders and to analyze the results depending on the indication leading to surgery. Fifty-six patients with various hematological disorders were splenectomized between 1990 and 1994. The main indication was noted. Operative success was defined as: return to normal platelet counts without further medication in thrombocytopenia, relief of pain and local compression syndrome in painful splenomegaly, hemogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…A signi cant proportion of splenectomised patients achieve long-term control of their disease with minimal morbidity and mortality [1,3,8,9]. In keeping with current literature, our study too yielded impressive overall survival rates with 98%.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…A signi cant proportion of splenectomised patients achieve long-term control of their disease with minimal morbidity and mortality [1,3,8,9]. In keeping with current literature, our study too yielded impressive overall survival rates with 98%.…”
Section: Discussionsupporting
confidence: 78%
“…Transfusion related complications like iron overload and its effects on various organs, risk of blood borne infections and related cost of healthcare only adds to this nancial burden. Splenectomy affords symptomatic relief and can reduce transfusion dependency in many [3][4][5][6][7], but is not without its risks, hence is considered as a therapeutic option only when absolutely necessary and the bene ts outweigh the risks.…”
Section: Discussionmentioning
confidence: 99%
“…The investigators from Germany recently reported the results of splenectomy in various hematological conditions, which were comparable to the literature with response rates of 60% and 78% in patients with AHA and thrombocytopenia, respectively [11]. These studies, however, failed to compare the results in idiopathic cases versus those with associated diseases.…”
Section: Discussionmentioning
confidence: 82%
“…The authors of the present study chose the latter. Platelet counts above 100,000 of steroids should be achieved in 75 to 80% of patients with ITP (1,3). In the present series (8), 9 of 15 (60%) patients with ITP met this criteria, whereas 3 still required steroids and 3 others were failures.…”
Section: S Grantmentioning
confidence: 99%